Storage of monokaryotic strains of Podospora anserina - Navtej Toor; Georg Hausner; Steven Zimmerly (Fungal Genetics Reports, 2001)
Maintenance of Podospora anserina strains for experimental purposes is very time consuming (see Esser 1969 Neurospora Newsl. 15:27-31) and methods have been published that address this issue by freezing ascospores at -80 oC (Begel and Belcour 1991 Fungal Genet. Newsl. 38:67). Although the latter approach does reduce the amount of time required for yearly sexual crosses and ascospore isolation, it does not resolve the problem of the time required to rapidly generate monokaryotic hyphae, that are needed as a source for inoculum for many types of experiments.